perspective, analogy, and contrast A philosophical approach to the concepts of place and vision in the pottery of Mesopotamia (Journal of the College of Basic Education, 2023)
The art of pottery intertwines its difficulty by thinking that it is seen and can be described visually, especiallyAfter we see the drawings added and sculpted on the old pottery, he can giveA visible image of the invisible thought ((So this means that the invisible can sometimes be visible?Yes, provided that the thought consists only of visual forms))